STAD atau Jigsaw? Menguji Keefektifan Dua Model Pembelajaran Kooperatif dalam PKn - Bahartiar, Bahartiar (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2024)
This study aims to determine the differences in Civic Education learning outcomes between students taught using the STAD cooperative learning model and the Jigsaw cooperative learning model at MAN 1 Kendari. The research method used is an experimental design with a post-test only control group design. The sample consists of 60 students, selected through multi-stage random sampling, with 30 students from class XI IPS2 and 30 students from class XI IPS3. Data were collected using a Civic Education learning outcomes test, which was validated and tested for reliability, with a reliability score of 0.903. The results showed that the average learning outcomes of students taught with the STAD model were higher (87.21) compared to those taught with the Jigsaw model (73.44). Hypothesis testing revealed a significant difference between the two learning models, with a t-value (30) greater than the t-table value (2.390) at a 0.01 significance level. This study concludes that the STAD cooperative learning model is more effective in improving Civic Education learning outcomes compared to the Jigsaw learning model.